Development of Thematic Worksheet Based on Character Education for Fifth Graders Schools - Sari Utami, Setia; Sukenda, Asep; Valen, Andri (Universitas Negeri Semarang, 2020)
This study aims to develop LKS in the form of Thematic Worksheet Based on Environmental Care Character Education on Theme 8